Complex mitonuclear interactions and metabolic costs of mating in male seed beetles. (28th November 2015) - Immonen, E.; Rönn, J.; Watson, C.; Berger, D.; Arnqvist, G.
Abstract: The lack of evolutionary response to selection on mitochondrial genes through males predicts the evolution of nuclear genetic influence on male‐specific mitochondrial function, for example by gene duplication and evolution of sex‐specific expression of paralogs involved in metabolic pathways. Intergenomic epistasis may therefore be a prevalent feature of the genetic architecture of male‐specific organismal function. Here, we assess the role of mitonuclear genetic variation for male metabolic phenotypes [metabolic rate and respiratory quotient (RQ)] associated with ejaculate renewal, in the seed beetle Callosobruchus maculatus, by assaying lines with crossed combinations of distinct mitochondrial haplotypes and nuclear lineages. We found a significant increase in metabolic rate following mating relative to virgin males. Moreover, processes associated with ejaculate renewal showed variation in metabolic rate that was affected by mitonuclear interactions. Mitochondrial haplotype influenced mating‐related changes in RQ, but this pattern varied over time. Mitonuclear genotype and the energy spent during ejaculate production affected the weight of the ejaculate, but the strength of this effect varied across mitochondrial haplotypes showing that the genetic architecture of male‐specific reproductive function is complex. Our findings unveil hitherto underappreciated metabolic costs of mating and ejaculate renewal, and provide the first empirical demonstration of mitonuclear epistasis on male reproductive metabolic processes.